Comparison of four functionalization methods of gold nanoparticles for enhancing the enzyme-linked immunosorbent assay (ELISA) - Ciaurriz, Paula; Fernández, Fátima; Tellechea, Edurne; Moran, Jose F.; Asensio, Aaron C. (Beilstein Journal of Nanotechnology, 2017)
The enzyme-linked immunosorbent assay (ELISA) technique is based on the specific recognition ability of the molecular structure of an antigen (epitope) by an antibody and is likely the most important diagnostic technique used today in bioscience. With this methodology, it is possible to diagnose illness, allergies, alimentary fraud, and even to detect small molecules such as toxins, pesticides, heavy metals, etc. For this reason, any procedures that improve the detection limit, sensitivity or reduce the analysis time could have an important impact in several fields. In this respect, many methods have been developed for improving the technique, ranging from fluorescence substrates to methods for increasing the number of enzyme molecules involved in the detection such as the biotin–streptavidin method. In this context, nanotechnology has offered a significant number of proposed solutions, mainly based on the functionalization of nanoparticles from gold to carbon which could be used as antibody carriers as well as reporter enzymes like peroxidase. However, few works have focused on the study of best practices for nanoparticle functionalization for ELISA enhancement. In this work, we use 20 nm gold nanoparticles (AuNPs) as a vehicle for secondary antibodies and peroxidase (HRP). The design of experiments technique (DOE) and four different methods for biomolecule loading were compared using a rabbit IgG/goat anti-rabbit IgG ELISA model (adsorption, directional, covalent and a combination thereof). As a result, AuNP probes prepared by direct adsorption were the most effective method. AuNPs probes were then used to detect gliadin, one of the main components of wheat gluten, the protein composite that causes celiac disease. With this optimized approach, our data showed a sensitivity increase of at least five times and a lower detection limit with respect to a standard ELISA of at least three times. Additionally, the assay time was remarkably decreased.
Keywords: allergen; ELISA enhancement; functionalization; gliadin; gold nanoparticle

(untitled) - Yalow, R. S.; Berson, S. A. (J. Clin. Invest., 1960)

(untitled) - Porstmann, T.; Kiessig, S. T. (J. Immunol. Methods, 1992)

(untitled) - Rebe Raz, S.; Haasnoot, W. (TrAC, Trends Anal. Chem., 2011)

Enzyme Immunoassays - Deshpande, S. S. (Springer, 1996)

(untitled) - Wu, W.; Li, J.; Pan, D.; Li, J.; Song, S.; Rong, M.; Li, Z.; Gao, J.; Lu, J. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Cao, X.; Ye, Y.; Liu, S. (Anal. Biochem., 2011)

(untitled) - Zhang, Q.; Zhao, B.; Yan, J.; Song, S.; Min, R.; Fan, C. (Anal. Chem., 2011)

(untitled) - Zhou, Y.; Tian, X.-L.; Li, Y.-S.; Pan, F.-G.; Zhang, Y.-Y.; Zhang, J.-H.; Yang, L.; Wang, X.-R.; Ren, H.-L.; Lu, S.-Y.; Li, Z.-H.; Chen, Q.-J.; et al. (Biosens. Bioelectron., 2011)

(untitled) - Oaew, S.; Charlermroj, R.; Pattarakankul, T.; Karoonuthaisiri, N. (Biosens. Bioelectron., 2012)

(untitled) - Shen, Z.; Hou, N.; Jin, M.; Qiu, Z.; Wang, J.; Zhang, B.; Wang, X.; Wang, J.; Zhou, D.; Li, J. (Gut Pathog., 2014)

(untitled) - Jiang, T.; Song, Y.; Wei, T.; Li, H.; Du, D.; Zhu, M.-J.; Lin, Y. (Biosens. Bioelectron., 2016)

(untitled) - Ambrosi, A.; Airò, F.; Merkoçi, A. (Anal. Chem., 2010)

(untitled) - Luo, Y.; Zhang, B.; Chen, M.; Jiang, T.; Zhou, D.; Huang, J.; Fu, W. (J. Transl. Med., 2012)

(untitled) - Song, S.; Qin, Y.; He, Y.; Huang, Q.; Fan, C.; Chen, H.-Y. (Chem. Soc. Rev., 2010)

(untitled) - Jans, H.; Huo, Q. (Chem. Soc. Rev., 2012)

(untitled) - Daniel, M.-C.; Astruc, D. (Chem. Rev., 2004)

(untitled) - Ciaurriz, P.; Bravo, E.; Hamad-Schifferli, K. (J. Colloid Interface Sci., 2014)

(untitled) - Tellechea, E.; Wilson, K. J.; Bravo, E.; Hamad-Schifferli, K. (Langmuir, 2012)

(untitled) - Fernández, F.; Sánchez-Baeza, F.; Marco, M.-P. (Biosens. Bioelectron., 2012)

(untitled) - Kumar, S.; Aaron, J.; Sokolov, K. (Nat. Protoc., 2008)

(untitled) - Puertas, S.; Batalla, P.; Moros, M.; Polo, E.; del Pino, P.; Guisán, J. M.; Grazú, V.; de la Fuente, J. M. (ACS Nano, 2011)

(untitled) - Aubin-Tam, M.-E.; Hamad-Schifferli, K. (Biomed. Mater. Bristol Engl., 2008)

(untitled) - Cifuentes-Rius, A.; de Puig, H.; Kah, J. C. Y.; Borros, S.; Hamad-Schifferli, K. (ACS Nano, 2013)

(untitled) - Mena, M. C.; Lombardía, M.; Hernando, A.; Méndez, E.; Albar, J. P. (Talanta, 2012)

(untitled) - Tjon, J. M.-L.; van Bergen, J.; Koning, F. (Immunogenetics, 2010)

(untitled) - Geoghegan, W. D.; Ackerman, G. A. (J. Histochem. Cytochem., 1977)

DOE Simplified: Practical tools for effective experimentation - Patrick, J.; Whitcomb, M. J. A. (CRC Press, 2015)

(untitled) - Geoghegan, W. D. (J. Histochem. Cytochem., 1988)

(untitled) - Nygren, H.; Hansson, H. A. (J. Histochem. Cytochem., 1981)

Bioconjugate Techniques - Hermanson, G. T. (Academic Press, 2013)

(untitled) - Rao, S. V.; Anderson, K. W.; Bachas, L. G. (Microchim. Acta, 1998)

(untitled) - Aubin-Tam, M.-E.; Hamad-Schifferli, K. (Langmuir, 2005)

Symposium O – Nanoparticles and Nanostructures in Sensors and Catalysis - Aubin-Tam, M. E.; Hamad-Schifferli, K. (MRS Online Proceedings Library Archive, 2005)

(untitled) - Gagner, J. E.; Lopez, M. D.; Dordick, J. S.; Siegel, R. W. (Biomaterials, 2011)

(untitled) - Zhan, L.; Wu, W. B.; Yang, X. X.; Huang, C. Z. (New J. Chem., 2014)